Elastin haploinsufficiency accelerates age-related structural and functional changes in the renal microvasculature and impairment of renal hemodynamics in female mice - Dixon, Alethia J.; Osei-Owusu, Patrick (Frontiers in Physiology, 2023)
Age-related decline in functional elastin is associated with increased arterial stiffness, a known risk factor for developing cardiovascular disease. While the contribution of elastin insufficiency to the stiffening of conduit arteries is well described, little is known about the impact on the structure and function of the resistance vasculature, which contributes to total peripheral resistance and the regulation of organ perfusion. In this study, we determined how elastin insufficiency impinges on age-related changes in the structure and biomechanical properties of the renal microvasculature, altering renal hemodynamics and the response of the renal vascular bed to changes in renal perfusion pressure (RPP) in female mice. Using Doppler ultrasonography, we found that resistive index and pulsatility index were elevated in young Eln+/- and aged mice. Histological examination showed thinner internal and external elastic laminae, accompanied by increased elastin fragmentation in the medial layer without any calcium deposits in the small intrarenal arteries of kidneys from young Eln+/- and aged mice. Pressure myography of interlobar arteries showed that vessels from young Eln+/- and aged mice had a slight decrease in distensibility during pressure loading but a substantial decline in vascular recoil efficiency upon pressure unloading. To examine whether structural changes in the renal microvasculature influenced renal hemodynamics, we clamped neurohumoral input and increased RPP by simultaneously occluding the superior mesenteric and celiac arteries. Increased RPP caused robust changes in blood pressure in all groups; however, changes in renal vascular resistance and renal blood flow (RBF) were blunted in young Eln+/- and aged mice, accompanied by decreased autoregulatory index, indicating greater impairment of renal autoregulation. Finally, increased pulse pressure in aged Eln+/- mice positively correlated with high RBF. Together, our data show that the loss of elastin negatively affects the structural and functional integrity of the renal microvasculature, ultimately worsening age-related decline in kidney function.